Avaliação da leishmaniose visceral canina em Poxoréo, Estado do Mato Grosso, Brazil - de Azevedo, Márcia Ávila [UNESP]; Dias, Ana Karina K. [UNESP]; de Paula, Henrique B. [UNESP]; Perri, Silvia Helena V. [UNESP]; Nunes, Cáris M. [UNESP] (My University, 2008)
Dogs play an important role as reservoir in the domestic cycle of visceral leishmaniasis, a serious public health problem. An epidemiological survey in 1,112 dogs was conducted at the Municipality of Poxoréo State of Mato Grosso, Brazil, using indirect immunofluorescence antibody test where the prevalence was 7.8%. Significant association was found between prevalence of canine visceral leishmaniasis and age of the dogs. Clinical signs and presence of other animals in the backyard, like chicken being more likely associated with seropositivity. Gender, garbage collection in the residence and family financial income were not associated with visceral leishmaniasis prevalence. Analysis of the results suggests that dogs aging more than 7 years and presence of another animal species co-inhabiting with the dogs may be risk factors for canine visceral leishmaniasis.
Canine visceral leishmaniasis evaluation in Poxoréo, Mato Grosso State, Brazil
Keywords: Dogs; Epidemiology; Prevalence; Risk factors